Water desorption isotherms and net isosteric heat of desorption on lignite. (1st May 2016) - Wan, Keji; He, Qiongqiong; Miao, Zhenyong; Liu, Xuejing; Huang, Shaomeng
Highlights: Desorption isotherms were applied to investigate the behaviour of water on coal. For a description of desorption process, the GAB model provided a good fit. The BET theory was used to calculate the net isosteric heat. There was interaction among adsorbed water molecules at the monolayer region. Abstract: Water vapor desorption isotherm studies were performed on lignite at the temperature 30, 40 and 50 °C to investigate the behavior of water on coal. For a description of desorption process, a Guggenheim–Anderson–de-Boer (GAB) model provided a good fit. At the monolayer region, the overlapping isotherms at different temperatures could not provide valid data to calculate the isosteric heat by applying the Clausius–Clapeyron equation, and hence the isosteric heat was only determined at the moisture content from 0.125 to 0.280 mg/mg dry coal. Then, the Brunner–Emmet–Teller (BET) theory was applied to calculate the isosteric heat at the moisture content below 0.125 mg/mg dry coal. Net isosteric heat of desorption determined from the isotherms increases from 1.88 kJ/mol in the capillary water to 8.17 kJ/mol at the monolayer region. This increase is most likely that the forces from coal surface act on all types of water in raw lignite, and as the moisture content decreases, the forces are becoming stronger. Besides, with the effect of the interaction among adsorbed water molecules and the bonding force between water molecules and active sites, at the monolayer region, a maximum energy peak appears on the curve of isosteric heat.